Sintesis asam 2-(2-(4-kloro-N-(2,6-Diklorofenil)benzamida) fenil)asetat sebagai salah satu turunan diklofenak yang merupakan kandidat obat penghambat COX (siklooksigenase) (Synthesis 2-(2-(4-Chloro-N-(2,6-dichlorophenil)benzamido)phenil)acetic acid as dic - Wahyu Novandari Herdiyanti; Ayik Rosita Puspaningtyas; Ika Oktavianawati (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Sodium diclofenac is an analgetic agent as an antimetabolite that used for treating pain. Several compound as a derivative diclofenac has been synthesis for increase its activity and reduce side effect. 2-(2-(4-Chloro-N-(2,6-dichlorophenyl) benzamido)phenyl)acetic acid is a derivate of Sodium diclofenac that synthesized for development new drugs. Synthesis 2-(2-(4-Chloro-N-(2,6-dichlorophenyl) benzamido)phenyl)acetic has benzoylation reaction between Sodium diclofenac and 4-Chlorobenzoil Chloride to give the target compound (2-(2-(4-Chloro-N-(2,6-dichlorophenyl) benzamido)phenyl)acetic acid).This compound has been purified by Column Chromatography and give yellow color with melting point 143-145oC and then fix identification by H-NMR 400 MHz and KBr FTIR. 2-(2-(4-Chloro-N-(2,6-dichlorophenyl) benzamido)phenyl)acetic acid can synthesized and resulted 8.39 % of yield. Keywords: Sodium diclofenac, 2-(2-(4-Chloro-N-(2,6-dichlorophenyl)benzamido)phenyl)acetic acid, pain.